Odong-Odong Apoteker: Maskot Baru untuk Sosialisasi GEMACERMAT - Andy Eko Wibowo; Rifki Febriansyah; Ingenida Hadning; Pinasti Utami; Aji Winanta (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Pharmacist Odong-Odong, Symbols, and Media Branding the Pharmacist's Existence in Indonesian Communities within the framework of the Drug Conscious Smart Society Movement (GEMACERMAT) is a movement based on the deterioration of the pharmacist's image in the last two years due to various cases in Indonesia. The goals of pharmacists odong-odong become symbols of the existence and role of pharmacists in society. The method used is making odong-odong in the form of a pharmacist holding a capsule, turning children's song lyrics into lyrics about basic knowledge of medicine that the public must know and introducing odong-odong as the new mascot of the pharmacists of IAI Bantul Branch members and pharmacists of IYPG members of the Yogyakarta Branch when they organizing community service activities. The result of this community service is that pharmacists odong-odong are created with various children's songs whose lyrics have been changed. The pharmacist odong-odong, was first used by the IAI when conducting antibiotic drug counseling at a healthy walk event in the framework of the 73rd Independence Day of the Republic of Indonesia organized by Karang Taruna Tanuditan Bantul. Odong-odong pharmacists have also been placed in several pharmacies belonging to IYPG member pharmacists. Pharmacists odong-odong become a favorite place for children to play while enjoying a song that contains knowledge about medicine. The songs are expected to enter the subconscious of the community and indirectly educate the use of drugs.Keywords: pharmacist; odong-odong; IYPG; IAI; GEMACERMAT.